Visibility of gingiva - An important determinant for an esthetic smile - Shipra Sepolia; Gaurav Sepolia; Rupinder Kaur; Devendar Kumar Gautam; Vikas Jindal; Subhash Chander Gupta (Wolters Kluwer Medknow Publications, 2014)
Background: Need for having better esthetics is the new emerging trend seen in patients' demands and expectations. Various periodontal procedures including the mucogingival procedures have been designed to enhance the esthetics. The amount of gingival display of the patient is also an important parameter while considering the esthetics of the patient. Till date, very few studies have been done in which the amount of gingival visibility have been determined. So, the aim of this study was to evaluate the amount of visibility of gingiva during natural smile and forced smile in the patients visiting Himachal Dental College and Hospital. Materials and Methods: A total of 400 patients (242 females and 158 males), aged between 18 to 49 years, attending the outpatient department of Himachal Dental College, were included in this study. Patients were divided into two groups according to age and gender. Clinical photographs of the patients were taken and analyzed according to the following classification: (1) Very high smile line that is more than 2 mm of marginal gingiva visible or more than 2 mm apical to the cementoenamel junction visible for the reduced but healthy periodontium, (2) high smile line that is between 0 and 2 mm of marginal gingiva visible or between 0 and 2 mm apical to the cementoenamel junction visible for the reduced but healthy periodontium, (3) average smile line in which only gingival embrasures are visible, (4) low smile line in which gingival embrasures and cementoenamel junction not visible. Examination of the gingiva was done for both natural smile and forced smile. Results: During smile analysis, the following results were revealed for Natural smile and forced smile. Natural smile analysis revealed following: C1: 1%, C2: 6%, C3: 43.50% and C4 was 49.50%. Forced smile analysis revealed the following: C1: 1%, C2: 15.50%, C3: 59% and C4: 24.50%. Conclusions: Excessive gingival display is an esthetic concern both to the patient and clinician. Therefore, understanding the etiology and treatment options is crucial for the treatment of such patients. So, it becomes utmost duty of the dentist to see that visual attractiveness of the smile is associated strongly with the health of the periodontium.